Short Term Results of Arthroscopic Repair of Subscapularis Tendon Tear - Zohreh Zafarani (Medical Journal of The Islamic Republic of Iran, 2009)
Background:Despite being the largest rotator cuff tendon of the shoulder,the function and clinical relevance of subscapularis pathology has been largely ignored in the literature.Although many studies have focused on subscapularis tears recently,majority of them reported techniques for open repair. The advent of arthroscopy and   arthroscopic repair techniques has opened new frontiers in the diagnosis and repair of torn rotator cuff tendons, including the subscapularis.In this article,we review shortterm results of arthroscopic subscapularis repair. Method: Ten patients with subscapularis tendon tear of the rotator cuff were studied   prospectively including 8 men and 2 women with an average age of 49.7±12.8 years and an average delay in treatment of 23.3 months. Clinical outcomes, including the UCLAscore were assessed in all patients after 3 months of the surgery. Results: 6 patients were followed regularly for more than 6 months,while other 4 patients had a follow-up period of more than a year. The pain score improved from 1.75 to 9 and the UCLA score from 8.8 to 30.6.Conclusions: rthroscopic repair of subscapularis tendon tear results in significant subjective and objective improvement and high levels of patient satisfaction.